Optimization Strategy of Village Organization Functions and Roles to Resilience Village of Covid-19 - Eduart Wolok; Funco Tanipu; Noval Talani; Jefriyanto Saud; Zul Fikar Ahmad; Sahrain Bumulo (International Journal on Integrated Education, 2022)
The impact of Covid-19 has devastated all aspects of human life. When this pandemic ends, the uncertainty requires all parties to formulate a practical and systematic long-term strategic model against Covid-19. All intervention models have been carried out, but they have not significantly impacted efforts to prevent Covid-19 transmission in the community. Therefore, this article examines the Covid-19 mitigation scenario explicitly based on local wisdom and the optimization of village organization institutions to prevent the spread of Covid-19 in the community. This study was conducted in Pohuwato Regency, Gorontalo Province, Indonesia using the descriptive analysis method. This study found to prevent the spread of Covid-19 at the level of a pluralistic village community and a powerful kinship system, a particular mitigation scenario based on the community's local wisdom is needed. Several mitigation scenarios can be implemented in Pohuwato Regency to prevent the spread of Covid-19 in rural communities, including 1) Communication strategy, 2) Socio-cultural analysis, 3) Public health perspective. This article concludes that local wisdom-based mitigation scenarios are a new approach in controlling the spread of Covid-19 in rural communities that are still closely related. Besides that, to become Resilience a Covid-19 Tangguh Village,